Peningkatan Pemahaman Mayarakat Pemberdayaan Limbah Organik Menjadi Pupuk Organik - Jesi Alexander Alim; Asian Trisnawati S; Vanesha Febri Wistamuger; Vivian Meilani Situmorang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
Organic waste is one of the wastes that can still be recycled into something more useful, including fertilizer.Fertilizer is a very important requirement for plants.Fertilizer is a source of energy for plant growth and survival because it contains various types of nutrients that are very important for plants.With a good fermentation process, organic waste such as vegetables, rotten fruits, and leaves can be used as fertilizer that supports plant growth.Socialization on the manufacture of organic waste is urgently needed at this time, given the importance of reducing organic waste which often causes a foul odor.Therefore, the service activities carried out by Kukerta Bandarraya are expected to be able to increase understanding